Using statistical analysis to study the most important causes of pollution in the Iraqi marsh areas - Omar Abdul Mohsen Ali; Huraa Hassan Attieh (Iraqi Journal for Administrative Sciences, 2024)
The need for detection and investigation of the causes of pollution of the marshes and submit a statistical study evaluated accurately and submitted to the competent authorities and to achieve this goal was used to analyze the factorial analysis and then obtained the results from this analysis from a sample selected from marsh water pollutants which they were: (Electrical Conductivity: EC, Power of Hydrogen: PH, Temperature: T, Turbidity: TU, Total Dissolved Solids: TDS, Dissolved Oxygen: DO). The size of sample (44) sites has been withdrawn and examined in the laboratories of the Iraqi Ministry of Environment. By illustrating SPSS program) the results had been obtained. The most important recommendation was to increase the pumping of additional quantity of water from the Marshlands to the former in a balanced manner with the rate of discharge of water to improve the quality of water and to reflect positively on the improvement of the environment to the announcement of "Ramsar" sites of international importance.